2005
DOI: 10.1096/fj.04-3309fje
|View full text |Cite
|
Sign up to set email alerts
|

PPAR‐gamma modulates allergic inflammation through up‐regulation of PTEN

Abstract: The ligand-activated nuclear receptor peroxisome proliferator-activated receptor gamma (PPARgamma) has been shown to regulate cell activation, differentiation, proliferation, and/or apoptosis. PPARgamma is also associated with anti-inflammatory responses. However, the signaling mechanism remains elusive. We have used a mouse model for asthma to determine the effect of PPARgamma agonists, rosiglitazone or pioglitazone, and PPARgamma on allergen-induced bronchial inflammation and airway hyperresponsiveness. Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 42 publications
5
125
0
2
Order By: Relevance
“…Additionally, pharmacological affinity studies have previously shown that of the 4 TZD's, Rosi has the highest affinity for PPARg, followed by Pioglitazone > Troglitazone > Ciglitazone. 29,30 Previously, PPARg agonists, in particular Rosi, have been shown to correlate with PTEN expression in MCF-7 breast cancer cells, 18 macrophages, 18 monocytes, 44 bronchoalveolar lavage cells 45 and AsPC-1 pancreatic cancer cells. 46 We show here that stimulation of MCF-7 cells with 30 lM Rosi results in a~1.5-fold increase in PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pharmacological affinity studies have previously shown that of the 4 TZD's, Rosi has the highest affinity for PPARg, followed by Pioglitazone > Troglitazone > Ciglitazone. 29,30 Previously, PPARg agonists, in particular Rosi, have been shown to correlate with PTEN expression in MCF-7 breast cancer cells, 18 macrophages, 18 monocytes, 44 bronchoalveolar lavage cells 45 and AsPC-1 pancreatic cancer cells. 46 We show here that stimulation of MCF-7 cells with 30 lM Rosi results in a~1.5-fold increase in PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…Rosiglitazone (1, 2.5, or 5 mg/kg body weight/day; GlaxoSmithKline) dissolved in distilled water or pioglitazone (1, 5, or 10 mg/kg body weight/ day; Takeda Chemical Industries) dissolved in 0.05% DMSO and diluted with saline, was administered by oral gavage at 24-h interval on days 36 -66, beginning 2 days before the first challenge as previously described (15) (Fig. 1).…”
Section: Administration Of Rosiglitazone Pioglitazone Gw9662 Ad Vementioning
confidence: 99%
“…1). A selective antagonist of PPAR␥, GW9662 (0.5 mg/kg body weight/day; Cayman) dissolved in PBS was administered intratracheally six times to each animal on days 37,40,47,54,61, and 67, beginning 1 day before the first challenge as previously described (15). Ad vectors were administered intratracheally (10 9 PFU) six times to each animal on days 37, 40, 47, 54, 61, and 65, beginning 1 day before the first challenge.…”
Section: Administration Of Rosiglitazone Pioglitazone Gw9662 Ad Vementioning
confidence: 99%
See 2 more Smart Citations